Positioning Culture within Canadian Municipalities - Dick, Ben; Jeannotte, M. Sharon; Hill, Kelly (Université d'Ottawa | University of Ottawa, 2019)
Although sometimes still referred to as ‘creatures of the province’, municipalities in Canada now shape their own policies in a number of complex areas. This includes culture, since municipal cultural planning has broadened the municipal role. While municipalities still provide‘cultural services’, such as arts centres and museums, cultural planning involves a more strategic role for the municipality in supporting the development of the local cultural sector, while integrating culture across many areas of municipal decision-making. The literature on organizational theory and design suggests that for municipal cultural planning to achieve these objectives, municipalities should adopt an organizational structure that supports this role. The Culture Position Study was initiated to better understand the different ways in which culture is currently situated within municipal organizational structures, and how these structures are evolving.
Keywords: Culture; Municipal; Cultural planning; Organization; Structure